KEAJAIBAN MEDIA AUDIOVISUAL: MENINGKATKAN MINAT BELAJAR ANAK SEKOLAH DASAR - Delta Srimayola, Putri Aurel Violeta, Nabila Aulia, Muhammad Arif Ridha, Audi Melia Praptikasari (CV. ADIBA AISHA AMIRA, 2024)
This study aims to determine the effectiveness of audio-visual learning media in increasing learning interest. The research method used is a quantitative approach, specifically a quasiexperimental design with a two-group design. In this study, an experiment will be conducted with 16 third-grade students from SD 06 Taluak IV Suku, divided into two groups: 8 students in the experimental group and 8 students in the control group. The 8 students in the experimental group will learn using audio-visual media. To conduct this research, the researcher measured and calculated the effectiveness of the learning method using audiovisual media through the Mann Whitney U test. An analysis was also carried out using the Ngain score test, which yielded a result of 16.51%, indicating that the learning method using audio-visual media is not effective in increasing students' learning interest. For the Mann Whitney U test, the result was 0.141 > 0.05, meaning the hypothesis is rejected, indicating no difference between the learning method using audio-visual media (experimental group) and those not using it (control group).